Effects of Climate Warming, North Atlantic Oscillation, and El Niño-Southern Oscillation on Thermal Conditions and Plankton Dynamics in Northern Hemispheric Lakes - Dieter Gerten; Rita Adrian (The Scientific World Journal)
Impacts of climate warming on freshwater ecosystems have been documented recently for a variety of sites around the globe. Here we provide a review of studies that report long-term (multidecadal) effects of warming trends on thermal properties and plankton dynamics in northern hemispheric lakes. We show that higher lake temperatures, shorter periods with ice cover, and shorter stagnation periods were common trends for lakes across the hemisphere in response to the warmer conditions. Only for shallow dimictic lakes was it observed that deep-water temperatures decreased. Moreover, it became evident that phytoplankton dynamics and primary productivity altered in conjunction with changes in lake physics. Algal spring blooms developed early and were more pronounced in several European lakes after mild winters with short ice cover periods, and primary productivity increased in North American lakes. Effects of elevated temperatures on zooplankton communities were seen in an early development of various species and groups, as is documented for cladocerans, copepods, and rotifers in European lakes. Furthermore, thermophile species reached higher abundance in warmer years.